Intrathecal enzyme replacement therapy reverses cognitive decline in mucopolysaccharidosis type I. Issue 3 (March 2017) - Nestrasil, Igor; Shapiro, Elsa; Svatkova, Alena; Dickson, Patricia; Chen, Agnes; Wakumoto, Amy; Ahmed, Alia; Stehel, Edward; McNeil, Sarah; Gravance, Curtis; Maher, Elizabeth
Abstract : Mucopolysaccharidosis type I (MPS I) is an inherited lysosomal storage disease that seriously affects the brain. Severity of neurocognitive symptoms in attenuated MPS subtype (MPS IA) broadly varies partially, due to restricted permeability of blood‐brain barrier (BBB) which limits treatment effects of intravenously applied α‐L‐iduronidase (rhIDU) enzyme. Intrathecal (IT) rhIDU application as a possible solution to circumvent BBB improved brain outcomes in canine models; therefore, our study quantifies effects of IT rhIDU on brain structure and function in an MPS IA patient with previous progressive cognitive decline. Neuropsychological testing and MRIs were performed twice prior (baseline, at 1 year) and twice after initiating IT rhIDU (at 2nd and 3rd years). The difference between pre‐ and post‐treatment means was evaluated as a percentage of the change. Neurocognitive performance improved particularly in memory tests and resulted in improved school performance after IT rhIDU treatment. White matter (WM) integrity improved together with an increase of WM and corpus callosum volumes. Hippocampal and gray matter volume decreased which may either parallel reduction of glycosaminoglycan storage or reflect typical longitudinal brain changes in early adulthood. In conclusion, our outcomes suggest neurological benefits of IT rhIDU compared to the intravenous administration on brain structure and function in a single MPS IA patient.© 2017 Wiley Periodicals, Inc.